Sistemas de terminação de novilhos de corte: bioeconomicidade e avaliação de modelos para a predição do desempenho animal - Silva, Alexandre Coradini Fontoura da (2007)
This work presents the bio-economical evaluation of beef cattle production systems used by farmers in the state of Rio Grande do Sul. Animal production, pasture dynamics and economically related results of two agriculturally integrated systems were studied according to topography, and a third system based on improved native pasture. In order to do this, steers were used, placed in paddocks previously sowed with annual ryegrass (Lolium multiflorum Lam.). Animal performance was also used for the evaluation of mathematical models according to accuracy in predicting weight gain, which may assist in choosing the most adequate system for each situation. It has been verified that the reduced input of insume in the pasture has made the production of forage smaller than the productive potential of this species, resulting in low animal stock rate. The forage masses have apparently caused limitations, in a certain period, to the intake of dry matter by the animal, still allowing expressive individual gains to be verified. The results from slaughterhouse productivity were obtained from carcass evaluation, applied to the analysis of system viability. Thus, only the systems that were preceded by crop production had positive economic results. Among the two mathematical models tested only one of them was capable of estimating adequately the animal live weight gain in the three production systems. The reduced forage masses above mentioned are appointed as a source of error to the models, even though the Pampa Corte model has been efficient in predicting animal performance in the three systems. It has been concluded that the farmer has alternatives for increasing beef cattle profit, among which production cost reduction brought through the integration between crop production, influence in the slaughter price variable, like the use of protection mechanisms against price oscillation and/or qualitative differentiation. Similarly, a series of factors that interfere in the increment of productive efficiency can be applied, using mathematical modelling as an auxiliary tool to quantify its effects.